Indices of cognitive function measured in rugby union players using a computer-based test battery - MacDonald, L. A.; Minahan, C. L. (Journal of Sports Sciences, 2016)
The purpose of this study was to investigate the intra- and inter-day reliability of cognitive performance using a computer-based test battery in team-sport athletes. Eighteen elite male rugby union players (age: 19 ± 0.5 years) performed three experimental trials (T1, T2 and T3) of the test battery: T1 and T2 on the same day and T3, on the following day, 24 h later. The test battery comprised of four cognitive tests assessing the cognitive domains of executive function (Groton Maze Learning Task), psychomotor function (Detection Task), vigilance (Identification Task), visual learning and memory (One Card Learning Task). The intraclass correlation coefficients (ICCs) for the Detection Task, the Identification Task and the One Card Learning Task performance variables ranged from 0.75 to 0.92 when comparing T1 to T2 to assess intraday reliability, and 0.76 to 0.83 when comparing T1 and T3 to assess inter-day reliability. The ICCs for the Groton Maze Learning Task intra- and inter-day reliability were 0.67 and 0.57, respectively. We concluded that the Detection Task, the Identification Task and the One Card Learning Task are reliable measures of psychomotor function, vigilance, visual learning and memory in rugby union players. The reliability of the Groton Maze Learning Task is questionable (mean coefficient of variation (CV) = 19.4%) and, therefore, results should be interpreted with caution.